Advances in paleoimaging : applications for paleoanthropology, bioarchaeology, forensics, and cultural artefacts - Beckett, Ronald G., 1953-; Conlogue, Gerald J. (Boca Raton : CRC Press, 2020)
Advances in Paleoimaging: Applications for Paleoanthropology, Bioarchaeology, Forensics, and Cultural Artifacts builds on the research and advances in technology since the writing of the authors' first book, Paleoimaging: Field Applications for Cultural Remains and Artifacts (ISBN: 978-1-4200-9071-0). Since Paleoimaging was published in 2009, additional research settings for the application of advanced imaging technologies have been identified. Practices are now more widespread and standardized with the capabilities and utilization of imaging methodologies increasing dramatically. Given the numerous advances in paleoimaging technique and technology, this book chronicles the evolution that has taken place in all the imaging modalities. Chapters include the coverage of magnetic resonance imaging, computed tomography, plane and digital radiography, endoscopy, and applications of x-ray fluorescence, as well as the principles of industrial radiography. While the book focuses on a multimodal imaging approach to anthropological and archaeological research, the authors and contributing authors have vast experience in other areas and present coverage of biological applications as well. The multidisciplinary chapters provide a foundation to understand the application of various imaging modalities in archaeological, anthropological, bioanthropological, and forensic settings. As such, Advances in Paleoimaging will serve as an essential reference for conservators, museum archivists, forensic anthropologists, paleopathologists, and archaeologists, who perform non-destructive research on historical or culturally significant artifacts, remains, or material from a forensic investigation. The concepts and methods presented in this text are supported with case presentations of the authors' vast experience in the new companion book, Case Studies for Advances in Paleoimaging (ISBN: 978-0-367-25166-6) by Beckett, Conlogue, and Nelson (2020).
OCLC-licensed vendor bibliographic record.
Keywords: Imaging systems in archaeology; LAW / Criminal Law / General; LAW / Forensic Science; SOCIAL SCIENCE / Anthropology / General